Endoscopic full-thickness resection for a gastrointestinal stromal tumor in a liver transplant recipient: A case report. Issue 31 (August 2019) - Xie, Man; Rao, Wei; Zhang, Peng; Zhao, Qingxi; Tian, Zibin
Abstract: Rationale: With the development of endoscopic technique and the improvement of available accessories, endoscopic therapy became to play an important role in the management of gastrointestinal submucosal tumors (SMTs). Patients concerns: A gastric SMT which was suspected to be gastrointestinal stroma tumor (GIST) was diagnosed in a liver transplant recipient who received transplanted operation 11 months ago. Diagnosis: gastric SMT, post-liver transplantation Interventions: Endoscopic full-thickness resection (EFR) was preformed to remove the tumor. The operation time was 50 minutes and oral immunosuppressant drug was not interrupted in the postoperative period. Outcomes: The clinical course was uneventful and slightly elevated liver enzyme was observed on the fourth day after operation. The pathological diagnosis was GIST with complete capsule. Lessons: Our successful experience showed that EFR is a feasible, safe and efficacious treatment for small (<2 cm) gastric GIST in liver transplant recipients, providing the advantages of little damage, short operative time, stable graft function, without compromising postoperative outcomes.